Changes in the Autonomic Nervous System in Patients with Carbon Monoxide Poisoning - A. V. Badalyan; G. N. Sukhodolova; Z. N. Marupov; A. N. Yelkov (Общая реаниматология)
Objective: to examine changes in the autonomic nervous system (ANS) function in patients with carbon monoxide poisoning in relation to the condition severity. Subjects and methods. The ANS was studied in 114 patients aged 15 to 82 years with carbon monohydrate poisoning who were treated at the N. V. Sklifosovsky Research Institute of Emergency Care, Moscow, in 2004—2008. Cardiointervalographic readings were analyzed in relation to the condition severity, the presence of thermal damages to the skin and upper airway, and that of blood alcohol. Results. Within the first hours after poisoning, the function of the ANS was found to be impaired, which was associated with the development of hypersympathicotonia caused by the increased activity of its sympathetic part and the decreased tone of the parasympathetic one. The magnitude of hypersympathicotonia depends on the severity of poisoning, on the presence of thermal damages to the upper respiratory tract and that of blood alcohol. The preponderance of the tone of the ANS parasympathetic part suggests the disturbance of adaptive and compensatory mechanisms and the likely poor prognosis of the poisoning. Conclusion. Cardiointervalography is recommended for the objective evaluation of the severity of carbon monoxide poisoning. Key words: carbon monoxide, autonomic nervous system, cardiointervalog-raphy, adaptive and compensatory mechanisms.